1997
DOI: 10.1007/bf01358743
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral body MRI related to lumbar fusion results

Abstract: The evaluation of continued pain after a technically successful posterolateral lumbar spine fusion is often challenging. Although the intervertebral disc is often a source of low back pain, abnormal endplates may also be a focus of pain, and possibly a source of continued pain after a posterolateral fusion. MRI allows noninvasive evaluation for disc degeneration, as well as for abnormal endplates and adjacent vertebral body marrow. Previous studies have found inflammatory marrow changes, adjacent to abnormal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 32 publications
3
17
1
1
Order By: Relevance
“…According to the model of Kirkaldy-Willis and Farfan, 16 segmental instability constitutes an intermediate stage in the natural history of lumbar degenerative disc disease, eventually leading to a final stage of decreased mobility and fixed deformity. Because it is generally accepted that Type 1 changes are strong markers of biomechanical instability while Type 2 changes reflect a more biomechanically stable environment, 6,7,10,23,29,33,37,38 our results therefore suggest that lumbar discectomy may lead to an accelerated transition from the stage of segmental instability to that of fixed deformity in the operated disc. This is further supported by the lower rate of chronic moderate low-back pain in the subgroup of patients exhibiting conversion to Type 2.…”
Section: Discussionmentioning
confidence: 58%
“…According to the model of Kirkaldy-Willis and Farfan, 16 segmental instability constitutes an intermediate stage in the natural history of lumbar degenerative disc disease, eventually leading to a final stage of decreased mobility and fixed deformity. Because it is generally accepted that Type 1 changes are strong markers of biomechanical instability while Type 2 changes reflect a more biomechanically stable environment, 6,7,10,23,29,33,37,38 our results therefore suggest that lumbar discectomy may lead to an accelerated transition from the stage of segmental instability to that of fixed deformity in the operated disc. This is further supported by the lower rate of chronic moderate low-back pain in the subgroup of patients exhibiting conversion to Type 2.…”
Section: Discussionmentioning
confidence: 58%
“…That these changes may reflect altered biomechanical stress is further supported by the observation that type 1 changes can convert to type 2 or a more normal-appearing marrow and that conversion is accelerated and possibly facilitated by fusion and instrumented stabilization. 17,[23][24][25][26] Six of our 16 patients with signal intensity resolution underwent conversion to a type 2 marrow change (Fig 5).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the persistence of type 1 Modic changes after fusion suggests pseudarthrosis. Buttermann et al 34 similarly observed that nonfusion was associated predominantly with the persistence of type 1 Modic changes. In a study of 56 patients treated with anterior lumbar interbody fusion for LBP, Chataigner et al 35 found that patients with type 1 Modic changes had much better outcomes than those with isolated DDD and those with type 2 changes, in whom the results were generally poor.…”
Section: Modic Changes and Segmental Instabilitymentioning
confidence: 95%
“…32 The relationship between Modic type 1 changes and segmental instability is mostly supported by indirect evidence coming from outcome studies following lumbar fusion. 26,[33][34][35][36] In a study assessing osseous union following lumbar fusion in 33 patients, Lang et al 33 found that all 19 patients with solid fusion had type 2 Modic changes, whereas 10 of 14 patients with nonunion had type 1 changes. They concluded that the persistence of type 1 Modic changes after fusion suggests pseudarthrosis.…”
Section: Modic Changes and Segmental Instabilitymentioning
confidence: 99%